IMPLEMENTATION MODEL OF RELIGIOUS MODERATION IN BOARDING SCHOOLS IN THE CONTEXT OF PETER L. BERGER'S THEORY OF SOCIAL CONSTRUCTION (STUDY AT ISLAMIC BOARDING SCHOOL IN EAST JAVA - INDONESIA) - M, Titik Triwulan Tutik (International Journal of Research -GRANTHAALAYAH, 2024)
This research is an Applied Research on National Strategic Studies, on the Implementation Model of Religious Moderation in Ma’had (Islamic boarding school) by taking case studies in Surabaya City, Probolinggo Regency, Jember Regency, and Sumenep Regency. Objectives of the activity: First, to analyze management patterns in implementing religious moderation in Ma’had. Second, to analyze the application of subject teacher (ustadz) learning in implementing religious moderation in Islamic boarding school (Ma’had) for their students. Third, describe the obstacles faced by Ma’had institutions in implementing religious moderation. The research design is designed as a field research design in which the researcher will conduct observations and interviews with the respondents, on the issues raised. These findings will be analyzed using the social construction theory of Peter L. Berger. The results of the study show: First, the management pattern in implementing religious moderation in Islamic boarding school/Ma’had begins with determining the vision and mission of the madrasa, and preparing the madrasa work program which is documented in the Ma’had Strategic Plan, Ma’had Work Plan, Annual Activity Plan, Ma’had Activity Plan and Budget, and Ma’had Curriculum. Second, Ma’had in implementing religious moderation generally use three patterns, namely: (1) integrating in the learning process; (2) habituation activities; (3) through extracurricular. Based on the implementation model of religious moderation at the Ma’had, it can generally be concluded that these patterns are following Peter L. Berger's Social Construction Theory, namely the existence of stages in implementation such as the preparation of vision and mission, work programs and habituation to the institution (process externalization), implementation of vision and mission, work programs, and habituation to Ma’had (objectification process), and a correct understanding of moderation and implementation in everyday life both in the school, home, and community environment (internalization process). Based on the findings/results of the research, the suggestions/recommendations that can be given are: (1) there needs to be socialization, workshops, technical guidance, training on religious moderation for all educators and education personnel in Ma’had in order to create a unified insight; (2) The government in this case the Ministry of Religion of the Republic of Indonesia needs to provide a separate budget related to religious moderation activities, especially in Ma’had so that activities can be carried out massively, systematically, and structured from the central level to the Ma’had level; and (3) Ma’had need to coordinate with parents through the madrasa committee, and carry out MoUs with stakeholders such as national private companies through CSR programs in implementing religious moderation in Ma’had, so that activities can be carried out massively and planned.